THEORETICAL ASPECTS OF ANALYSIS OF THE CONCEPT OF THE PRECARIAT IN THE CONTEXT OF CLASS THEORIES - Ya. O. Demonova (Вестник университета)
Theoretical analysis of the new social class of the precariat has been carried out and its scientific status has been clarified. The analysis has been undertaken from the standpoint of basic class theories. Three main approaches to determining the status of a precariat have been considered: the precariat as part of the proletariat, the precariat as a stratum, and the precariat as a separate class. The perfomed analysis shows that the precariat does not fully correspond to any class theory (in all cases certain social groups are excluded from it). The specifics of the precariat, its place and role in modern society do not allow us make an unequivocal conclusion about its status and the people included in it. In this regard an example of the author’s definition of the precariat, which can be used to conduct empirical research on this issue has been given in the article.